2015
DOI: 10.4274/jcrpe.1969
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function in Newborns with Congenital Hypothyroidism: Association with Thyroid-Stimulating Hormone Levels

Abstract: Objective:The aims of this study were to demonstrate ventricular function changes in patients with congenital hypothyroidism and to investigate whether there is an association between any such changes and thyroid-stimulating hormone (TSH) levels using M-mode and Doppler electrocardiography (ECG) and tissue Doppler imaging (TDI).Methods:Twenty-seven patients 5-30 days of age with congenital hypothyroidism who were scheduled to receive L-thyroxine treatment and 20 healthy newborns were included in this study. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…All of the above studies were based on the general population. The relationship between TSH level and cardiovascular function was also confirmed in new-born infants with congenital hypothyroidism [35]. However, to date, there is no report on the association between TSH level and maternal cardiovascular function during pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…All of the above studies were based on the general population. The relationship between TSH level and cardiovascular function was also confirmed in new-born infants with congenital hypothyroidism [35]. However, to date, there is no report on the association between TSH level and maternal cardiovascular function during pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to an increased risk of congenital heart disease ( 86–88 ), neonates with untreated CH may have increased aortic intimal-media thickness (IMT), serum cholesterol levels ( 197 ), and impaired cardiac function ( 198 , 199 ) reversed by early LT4 treatment ( 200 ).…”
Section: Outcomes Of Neonatal Screening and Early Treatmentmentioning
confidence: 99%
“…[11] In neonatal studies, it was found that congenital hypothyroidism can reduce the left ventricular systolic function and increase the risk of arrhythmia in newborn. [15] It is known that thyroid hormones play a significant role in regulating cardiac, vascular, and metabolic physiology. [12,14] In utero life is like a simulation of real life.…”
Section: Discussionmentioning
confidence: 99%